Communication privacy management theory in the context of the COVID-19 Pandemic: case studies from the Philippines - Bernabe, Edna T.; Pasumbal, Divina T.; Bernabe Jr., Mamerto S.; Pasumbal, Leia Reyna T. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Jurnal Komunikasi: Malaysian Journal of Communication Jilid 40(1) 2024: 496-512 *Corresponding author: bernabe.niniedna@gmail.com E-ISSN: 2289-1528 https://doi.org/10.17576/JKMJC-2024-4001-28 Communication Privacy Management Theory in the Context of the COVID-19 Pandemic: Case Studies from the Philippines EDNA T. BERNABE* DIVINA T. PASUMBAL MAMERTO S. BERNABE JR. LEIA REYNA T. PASUMBAL Polytechnic University of the Philippines ABSTRACT Information management during the COVID-19 pandemic ranges from personal to institutional level of agencies. This was highly observable at the onset of the national health emergency in the Philippines when most Filipinos who had symptoms did not know what to do. They, as well as their relatives, were in a fearful situation, and so were the government and private agencies involved in health care services. When in need of medical attention, will they tell the truth about their travel history or their exposure to anyone who is infected?